2005
DOI: 10.1093/eurheartj/ehi682
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial asynchronism is a determinant of changes in functional mitral regurgitation severity during dynamic exercise in patients with chronic heart failure due to severe left ventricular systolic dysfunction

Abstract: Changes in MR are variable during dynamic exercise. LV asynchronism at rest substantially contributes to worsening of functional MR during dynamic exercise in patients with CHF due to LV systolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 15 publications
3
29
1
Order By: Relevance
“…In normals, the relative mitral annulus circumference length and width proved to be 6.8 ± 0.8 cm and 4.2 ± 0.8 cm respectively, giving a ratio of 1.62, compared with the dilated cardiomyopathy patients, whose dimensions were 8.3 ± 1.8 cm and 5.8 ± 1.1 cm respectively, giving a ratio of 1.42 (p b 0.001). This reduced ratio in patients with dilated left ventricle is consistent with disturbance in mitral valve function and the development of mitral regurgitation, known for its clinical complications and poor prognosis [11][12][13]. Furthermore, others have shown that the structure and function of the tricuspid and mitral annuli are not independent of each other but are based around the golden ratio of 1.618 [14,15].…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 53%
“…In normals, the relative mitral annulus circumference length and width proved to be 6.8 ± 0.8 cm and 4.2 ± 0.8 cm respectively, giving a ratio of 1.62, compared with the dilated cardiomyopathy patients, whose dimensions were 8.3 ± 1.8 cm and 5.8 ± 1.1 cm respectively, giving a ratio of 1.42 (p b 0.001). This reduced ratio in patients with dilated left ventricle is consistent with disturbance in mitral valve function and the development of mitral regurgitation, known for its clinical complications and poor prognosis [11][12][13]. Furthermore, others have shown that the structure and function of the tricuspid and mitral annuli are not independent of each other but are based around the golden ratio of 1.618 [14,15].…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 53%
“…Exercise variably affects functional MR, and the severity of functional MR at rest does not predict MR response to exercise. 12 Exercise-induced MR results in a decrease in FSV and thereby exercise capacity in patients with LV systolic dysfunction. 6 Resting and dynamic LV dyssynchrony (as assessed by tissue Doppler imaging) strongly predict worsening of functional MR during exercise, 12,25 in addition to inducible myocardial ischemia 26 or local LV remodelling resulting in increased dynamic leaflet tethering.…”
Section: Discussionmentioning
confidence: 99%
“…12 Exercise-induced MR results in a decrease in FSV and thereby exercise capacity in patients with LV systolic dysfunction. 6 Resting and dynamic LV dyssynchrony (as assessed by tissue Doppler imaging) strongly predict worsening of functional MR during exercise, 12,25 in addition to inducible myocardial ischemia 26 or local LV remodelling resulting in increased dynamic leaflet tethering. 27 By enhancing LV +dP/dt 2-fold, CRT increases mitral force closures that offset the detrimental effects of exercise on functional MR. 7 In our patients with MR at rest, attenuation of exercise-induced MR improved exercise FSV and exercise cardiac output, whereas CRT did not affect the FSV and cardiac output responses to exercise in patients without MR at rest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, a decrease in regurgitant flow is associated with an improved forward stroke volume and thereby end-organ perfusion. Besides increased loading conditions, active myocardial ischemia contributes to worsening secondary MR, while medical and nonpharmacological treatments including revascularization and cardiac resynchronization therapy reduce the amount of MR [19,20,21,22,23,24]. A major feature of secondary MR in HFrEF is its dynamic nature with exercise.…”
Section: Secondary Mr In Hfrefmentioning
confidence: 99%